Plasma cytokines associated with febrile status epilepticus in children: A potential biomarker for acute hippocampal injury. (27th April 2017) - Gallentine, William B.; Shinnar, Shlomo; Hesdorffer, Dale C.; Epstein, Leon; Nordli, Douglas R.; Lewis, Darrell V.; Frank, L. Matthew; Seinfeld, Syndi; Shinnar, Ruth C.; Cornett, Karen; Liu, Binyi; Moshé, Solomon L.; et al.
Summary: Objective: Our aim was to explore the association between plasma cytokines and febrile status epilepticus (FSE) in children, as well as their potential as biomarkers of acute hippocampal injury. Methods: Analysis was performed on residual samples of children with FSE (n = 33) as part of the Consequences of Prolonged Febrile Seizures in Childhood study (FEBSTAT) and compared to children with fever (n = 17). Magnetic resonance imaging (MRI) was obtained as part of FEBSTAT within 72 h of FSE. Cytokine levels and ratios of antiinflammatory versus proinflammatory cytokines in children with and without hippocampal T2 hyperintensity were assessed as biomarkers of acute hippocampal injury after FSE. Results: Levels of interleukin (IL)‐8 and epidermal growth factor (EGF) were significantly elevated after FSE in comparison to controls. IL‐1β levels trended higher and IL‐1RA trended lower following FSE, but did not reach statistical significance. Children with FSE were found to have significantly lower ratios of IL‐1RA/IL‐1β and IL‐1RA/IL‐8. Specific levels of any one individual cytokine were not associated with FSE. However, lower ratios of IL‐1RA/IL‐1β, IL‐1RA/1L‐6, and IL‐1RA/ IL‐8 were all associated with FSE. IL‐6 and IL‐8 levels were significantly higher and ratios of IL‐1RA/IL‐6 and IL‐1RA/IL‐8 were significantly lower in children with T2 hippocampal hyperintensity on MRI after FSE in comparison to those without hippocampal signal abnormalities. Neither individual cytokine levels nor ratios of IL‐1RA/IL‐1β or IL‐1RA/IL‐8 were predictive of MRI changes. However, a lower ratio of IL‐1RA/IL‐6 was strongly predictive (odds ratio [OR] 21.5, 95% confidence interval [CI] 1.17–393) of hippocampal T2 hyperintensity after FSE. Significance: Our data support involvement of the IL‐1 cytokine system, IL‐6, and IL‐8 in FSE in children. The identification of the IL‐1RA/IL‐6 ratio as a potential biomarker of acute hippocampal injury following FSE is the most significant finding. If replicated in another study, the IL‐1RA/IL‐6 ratio could represent a serologic biomarker that offers rapid identification of patients at risk for ultimately developing mesial temporal lobe epilepsy (MTLE).